2008
DOI: 10.1021/ja801731g
|View full text |Cite
|
Sign up to set email alerts
|

Direct Evidence for Deprotonation of a Lysine Side Chain Buried in the Hydrophobic Core of a Protein

Abstract: We report direct evidence for deprotonation of a lysine side chain buried in the hydrophobic core of a protein, demonstrating heteronuclear 1H-15N NMR data on the Lys-66 side chain amine (Nzeta) group in the delta-PHS/V66K variant of staphylococcal nuclease. Previous crystallographic study has shown that the Lys-66 Nzeta group is completely buried in the hydrophobic core. On the basis of double and triple resonance experiments, we found that the 1Hzeta and 15Nzeta chemical shifts at pH 8.0 and 6 degrees C for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
107
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(113 citation statements)
references
References 15 publications
5
107
1
Order By: Relevance
“…In HIV-2 MA, Glu12 is substituted by Lys. Previous studies have shown that the p K a value of a buried Lys residue can be abnormally low (∼5.6) compared to Lys residues that are usually found at the surface and interact extensively with water (p K a = ∼10.5) (87). In this case, Lys side chain is present in the neutral state (NH 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…In HIV-2 MA, Glu12 is substituted by Lys. Previous studies have shown that the p K a value of a buried Lys residue can be abnormally low (∼5.6) compared to Lys residues that are usually found at the surface and interact extensively with water (p K a = ∼10.5) (87). In this case, Lys side chain is present in the neutral state (NH 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Here, through the combination of long-range 15 NÀ 13 C scalar J-coupling measurements and an atomic-detail molecular dynamics (MD) simulation, direct insight into the structural dynamic behavior of lysine side chains in human ubiquitin has been gained. On the basis of 1 H/ 13 C/ 15 N heteronuclear correlation experiments selective for lysine NH 3 þ groups, we analyzed two different types of long-range 15 NÀ 13 C J-coupling constants: one between intraresidue 15 Nζ and 13 Cγ nuclei ( 3 J NζCγ ) and the other between 15 Nζ and carbonyl 13 C 0 nuclei across a hydrogen bond ( h3 J NζC 0 ). The experimental 3 J NζCγ data confirm the highly mobile nature of the χ 4 torsion angles of lysine side chains seen in the MD simulation.…”
Section: B S Supporting Informationmentioning
confidence: 99%
“…In other cases, the presence of polar or charged residues in unfavorable, hydrophobic regions can have detrimental consequences for protein stability and/or function 3,4 . Furthermore, many of the permissible mutations which place an ionizable residue in the hydrophobic core of a protein are accompanied by pK a shifts which render side chain non-charged 5,6 . In similar fashion, burying a polar amino acid in the hydrophobic interior of a lipid bilayer membrane can be challenging.…”
Section: Introductionmentioning
confidence: 99%